EFFECT OF COBALT-CHROMIUM ALLOY RE-USE IN DENISTRY ON ITS CASTABILITY VALUE - Imran, Mehreen; Raza, Muhammad; Khan, Muhammad Sartaj; Hayat, Yousaf (Journal of Ayub Medical College Abbottabad, 2017)
Background: Re-use of dental casting alloy is a routine practice, which is carried out with the motive to conserve resources. There have been studies on the re-use of alloys but a controversy exists as to the proportioning ratio of fresh to used alloy and the number of time an alloy can be recast. The objective of the study was to measure the effect of addition of 50% by weight used alloy to the fresh Cobalt-Chromium alloy on the castability. Methods: In the present in-vitro experimental study A total of 20 specimens were cast by flame centrifuge, using modified Whitlock’˜s method. The total sample size was divided into four groups of five specimens each. Group 1 was the control group with 100% fresh alloy cast once. In group 2, 3 and 4, a 50% by weight cut off of previous castings were mixed to the fresh alloy. The re-used alloy for the group 2 and 3 was further aged or exposed to flame casting separately. The number of completely cast segments were counted and castability value was calculated according to the Whitlock’˜s formula. Result: There was no significant difference of castability value among all the tested group (p=0.085). Conclusion: Within the limitations of the present study, it is recommended that commercial Co-Cr-Mo alloy can be re-used six times without affecting its castability, when 50% fresh alloy is added on each re-use. Keywords: Castability; Cobalt; Chromium; Alloy